Kinetic Study of SN2 Reaction between Paranitrophenyl Benzoate and Hydrazine in the Presence of CTAB Reverse Micelles - K. Bhargavi; P. Shyamala; M. Padma; K. V. Nagalakshmi (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2021)
Kinetic study of the reaction between p-Nitrophenyl benzoate (PNPB) by hydrazine (HYN) in the presence of Cetyltrimethylammonium bromide (CTAB)/Chloroform/Hexane reverse micellar medium shows that the reaction obeys first order kinetics with respect to each of the reactants. The rate of the reaction is much slower in reverse micellar medium compared to aqueous medium under identical conditions (kˈAq = 2.84×10−3 sec−1, krm =1.34×10−4 sec−1). The rate constants for the reaction in the reverse micellar medium have been determined at different values of W W=[H2O]/[CTAB] and at different concentrations of CTAB. It was found that the observed rate constant decreases with W. This kinetic behaviour was interpreted by using modified Berezin pseudo phase model, taking into consideration the distribution of the reactants, PNPB and hydrazine between the three pseudo phases, i.e., water pool, interface an organic phase. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).